Case Report: Resection of Giant Endotracheal Hamartoma by Electrosurgical Snaring via Fiberoptic Bronchoscopy in a 9-Year-Old Boy - Wu, Lei; Chen, Wei; Li, PengCheng; Li, Shuxian; Chen, Zhimin (Frontiers in Pediatrics, 2021)
Endotracheal hamartomas are rarely encountered in children. The symptoms of endotracheal hamartoma may include cough, dyspnea, hemoptysis, chest pain, purulent sputum, and fever. The non-specific symptoms often result in a delayed diagnosis. Among the various treatments of this rare disease, surgical resection seems to be the most widely used, while endoscopic treatment is rarely described. Herein, we describe the case of a 9-year-old boy with an endotracheal hamartoma that was successfully excised by electrosurgical snaring via fiberoptic bronchoscopy (FB). The resection of select benign endotracheal tumors in children can be conducted using electrocautery, which can be regarded as an alternative therapy to bronchotomy.